Effect of ENaC modulators on rat neural responses to NaCl. - Shobha Mummalaneni; Jie Qian; Tam-Hao T Phan; Mee-Ra Rhyu; Gerard L Heck; John A DeSimone; Vijay Lyall (PLoS ONE, 2014)
The effects of small molecule ENaC activators N,N,N-trimethyl-2-((4-methyl-2-((4-methyl-1H-indol-3-yl)thio)pentanoyl)oxy)ethanaminium iodide (Compound 1) and N-(2-hydroxyethyl)-4-methyl-2-((4-methyl-1H-indol-3-yl)thio)pentanamide (Compound 2), were tested on the benzamil (Bz)-sensitive NaCl chorda tympani (CT) taste nerve response under open-circuit conditions and under ±60 mV applied lingual voltage-clamp, and compared with the effects of known physiological activators (8-CPT-cAMP, BAPTA-AM, and alkaline pH), and an inhibitor (ionomycin+Ca2+) of ENaC. The NaCl CT response was enhanced at -60 mV and suppressed at +60 mV. In every case the CT response (r) versus voltage (V) curve was linear. All ENaC activators increased the open-circuit response (ro) and the voltage sensitivity (κ, negative of the slope of the r versus V curve) and ionomycin+Ca2+ decreased ro and κ to zero. Compound 1 and Compound 2 expressed a sigmoidal-saturating function of concentration (0.25-1 mM) with a half-maximal response concentration (k) of 0.49 and 1.05 mM, respectively. Following treatment with 1 mM Compound 1, 8-CPT-cAMP, BAPTA-AM and pH 10.3, the Bz-sensitive NaCl CT response to 100 mM NaCl was enhanced and was equivalent to the Bz-sensitive CT response to 300 mM NaCl. Plots of κ versus ro in the absence and presence of the activators or the inhibitor were linear, suggesting that changes in the affinity of Na+ for ENaC under different conditions are fully compensated by changes in the apical membrane potential difference, and that the observed changes in the Bz-sensitive NaCl CT response arise exclusively from changes in the maximum CT response (rm). The results further suggest that the agonists enhance and ionomycin+Ca2+ decreases ENaC function by increasing or decreasing the rate of release of Na+ from its ENaC binding site to the receptor cell cytosol, respectively. Irrespective of agonist type, the Bz-sensitive NaCl CT response demonstrated a maximum response enhancement limit of about 75% over control value.